PEMBUATAN BIOETANOL DARI MINUMAN SERBUK AFKIR - Wiludjeng Trisasiwi (AGROINTEK, 2016)
Bioethanol can be made from three kinds of materials which contains glucose, starch, and cellulose. The creation of bioethanol from glucose substance considered the easiest because only needs two-stage process, fermentation and distillation. Nowadays, the creation of bioethanol from glucose and starch creates new problem due to the demand of the glucose and starch for food needs. Therefore, the non-food sources bioethanol should be found. One of them is from expired date powder beverage. The purpose of the research is to compare the bioethanol creation process using two kinds of distillation equipment. The analysis consist of yield and the purity of the bioethanol. Fermentation is carried out for 14 days using a 0.5% Fermipan yeast, Urea and TSP fertilizers. One time distillation using equipment with controlled temperature about 78oC for 6 hours produced bioethanol yield 20% and 95% purity. The simpler distillation tools without temperature controls, due 21.5% bioethanol, with 80% purity in twice distillation process. It can be concluded that controlled temperature at the ethanol's boiling point during the distillation process, produces higher yield and purity of the bioethanol also faster processing time. If the distillation temperature is too high, there will be lots of evaporated bioethanol to the ambient and water will evaporated and condensed, so the ethanol purity will be lesser.